Implementation of a Patient Safety Policy in Hospitalisation of Surgical Cases - Kristiani, Rina Budi; Orizani, Chindy Maria; Iswati, Iswati; Qomariah, Siti Nur; Bakar, Abu; Yobel, Sosilo (Scripta Medica, 2025)
Background/Aim: The Seven Steps to Patient Safety is a reference guide for hospitals implementing a patient safety program. The seven steps are building awareness of the value of patient safety, leading and supporting staff, integrating risk reporting activities, developing reporting systems, involving and communicating with patients, learning and sharing experiences about patient safety and preventing injuries through the implementation of patient safety systems. The purpose of this study was to evaluate the implementation of a patient safety policy in the hospitalisation of surgical medical cases.Methods: In this cross-sectional research, 360 nurses from several Gresik City public and private hospitals participated. Questionnaires on the application of the patient safety policy and a questionnaire that modified the seven steps of patient safety as implemented by nurses in the medical-surgical inpatient wards were used as the study instruments. Multiple logistic regression analysis was used to examine the data.Results: Most nurses have worked in medical-surgical for 6-10 years with work hours 40-59 every week. Implementation of patient safety had negative responses from nurses in Step 3 (integrated risk management) and Step 5 (open communication to patients and families). The simple logistic regression results for all steps were significant. Therefore, multiple logistic regression has shown that steps 1, 2, 4, 6 and 7 were significant to the implementation of patient safety policies.Conclusions: Patient safety policy remains a shared commitment that needs to be implemented. Hospitals as healthcare institutions that directly treat patients must prioritise safe, quality, anti-discriminatory and effective health services, prioritising the interests of patients according to hospital service standards.
Keywords: Evaluation; Hospital medicine; Patient safety; Policy